"First—Mind Rich, Second—Pocket Rich": Art as a Means to Revitalize Declining Community; The Case Study of Gejia Village. Issue 4 (20th October 2022) - Rega, Artur Piotr; Gimbut, Magdalena
Abstract : Using the example of Gejia village, the article concentrates on art-inspired activities used to revitalize rural areas in China. In particular, it analyzes the sociocultural context in which an art program was introduced. We try to answer also the question of whether art-led activities are a proper method to achieve civilizational and economic enhancement. The article describes how the program helped to revitalize relationships with the place, how the changes in material surroundings influenced the relations among people, and how they reshaped the bonds connecting people with their natural surroundings. We present practical results which might inspire other practitioners. The research is based on qualitative and detailed interviews and observations conducted in the village.